Penerapan Terapi Ankle Pump Exercise dan Elevasi Kaki 30 Derajat untuk Mengurangi Derajat Edema pada Pasien Gagal Ginjal Kronis dengan Masalah Keperawatan Hipervolemia di Ruang Hemodialisa RSD Gunung Jati Kota Cirebon 2026 - Bintang Rolistiani; Nonok Karlina (CV. ALIM'SPUBLISHING, 2026)
Chronic kidney disease is a permanent and progressive loss of kidney function in maintaining fluid-electrolyte balance and metabolism, resulting in azotemia and uremia (retention of urea, nitrogen, and waste products in the blood). This scientific study aims to analyze nursing care through the application of ankle pump exercise therapy and 30-degree leg elevation in a client with chronic kidney failure and a nursing issue of hypervolemia. The method applied in this study is the case study method. The subject of this scientific study was one client with chronic kidney failure and a nursing problem of hypervolemia who was undergoing treatment in the Hemodialysis Unit at Gunung Jati Regional General Hospital in Cirebon City. Data collection utilized interview, observation, and physical examination techniques. The nursing care process for the client spanned 2 days, and the assessment revealed edema in both lower extremities. The innovative intervention provided consisted of ankle pump exercise therapy through dorsiflexion and plantarflexion movements of the ankle, combined with 30-degree leg elevation in accordance with standard operating procedures. The results of the intervention showed a reduction in the degree of edema in both of the patient’s lower extremities following the ankle pump exercise therapy and 30-degree leg elevation. This intervention helped improve venous return, facilitate peripheral circulation, and reduce fluid accumulation.